2013
DOI: 10.1515/fhep-2012-0037
|View full text |Cite
|
Sign up to set email alerts
|

Better Quality of Care or Healthier Patients? Hospital Utilization by Medicare Advantage and Fee-for-Service Enrollees

Abstract: Do differences in rates of use among managed care and Fee-for-Service Medicare beneficiaries reflect selection bias or successful care management by insurers? I demonstrate a new method to estimate the treatment effect of insurance status on health care utilization. Using clinical information and risk-adjustment techniques on data on acute admission that are unrelated to recent medical care, I create a proxy measure of unobserved health status. I find that positive selection accounts for between one-quarter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…21 Moreover, since 2003 both groups have experienced similar declines in overall mortality, lending support to the conclusion that the observed changes among the Fee-for-Service population are not the result of changes in the risks of the groups relative to each other and do represent true improvement. Moreover, other studies have found that healthier people are likely to shift enrollment from Fee-for-Service to Medicare Advantage, which may have led to an underestimation of the improvement over time, 22,23 because we observed increasing enrollment in Medicare Advantage over time.…”
Section: Discussionmentioning
confidence: 60%
“…21 Moreover, since 2003 both groups have experienced similar declines in overall mortality, lending support to the conclusion that the observed changes among the Fee-for-Service population are not the result of changes in the risks of the groups relative to each other and do represent true improvement. Moreover, other studies have found that healthier people are likely to shift enrollment from Fee-for-Service to Medicare Advantage, which may have led to an underestimation of the improvement over time, 22,23 because we observed increasing enrollment in Medicare Advantage over time.…”
Section: Discussionmentioning
confidence: 60%
“…Capitated payments create financial incentives for MA plans to reduce hospitalizations, including readmissions, and to lower the intensity of services provided during inpatient stays. MA plans can achieve these goals through managed care tools including care coordination, information sharing, steering patients to lower cost providers in lower intensity settings (Nicholas, 2013), utilization management, and reimbursing hospitals at rates that reflect the value of services, which may be lower than TM rates (Baker, Bundorf, Devlin, & Kessler, 2016). MA plans can also attempt to "cherry-pick" healthier beneficiaries less likely to need inpatient care, although Centers for Medicare & Medicaid Services (CMS) payment adjustments based on enrollee demographics and health status work toward neutralizing this incentive.…”
Section: Introductionmentioning
confidence: 99%
“…1 The original proponents of MA saw the potential for improved quality of care, which could lead to better health outcomes when compared with those of FFS Medicare. 2 However, the ability of MA to achieve these goals has not been fully demonstrated. A recent systematic review published by the Kaiser Family Foundation described the evidence regarding the relative impact of MA on actual objective health outcomes and mortality as outdated and characterized by insufficient control for selection bias.…”
Section: Introductionmentioning
confidence: 99%